2017
DOI: 10.4269/ajtmh.16-0777
|View full text |Cite
|
Sign up to set email alerts
|

Chagas Disease Infection among Migrants at the Mexico/Guatemala Border

Abstract: Chagas disease results in the largest burden, in terms of disability-adjusted-life-years, of any parasitic disease in the Americas. Monitoring Chagas disease among migrants is critical to controlling its spread and to serving the needs of the migrant community. Therefore, we determined the prevalence and correlates of Chagas disease in regional and international migrant populations at the Mexico/Guatemala border. Data were collected as part of a larger study of human immunodeficiency virus (HIV) and migration.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
2
14
0
1
Order By: Relevance
“…The barriers found in Japan included language barrier, migratory process, and difficulties to access the health care system. These results are similar to the barriers experienced by the LA migrant population in other non-endemic countries [30, 11, 17, 31].…”
Section: Discussionsupporting
confidence: 86%
“…The barriers found in Japan included language barrier, migratory process, and difficulties to access the health care system. These results are similar to the barriers experienced by the LA migrant population in other non-endemic countries [30, 11, 17, 31].…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, among a sample of migrants at the Guatemala-Mexico border, 80% had not previously heard of CD [12].…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has found a high degree of socioeconomic marginalization among immigrants with CD in Europe and the United States [9][10]. Despite having a higher risk for CD, immigrants from Latin America are typically undiagnosed and may not have heard of the disease [11][12]. Compounding this, providers in host countries are often unfamiliar with CD and not up-to-date with treatment recommendations [13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical manifestations of this disease can be distinguished into an acute phase which lasts 6-8 weeks and chronic phases [107]. In these acute cases, patients are often found to have fever, malaise, headache, and hepatosplenomegaly [1].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…In these acute cases, patients are often found to have fever, malaise, headache, and hepatosplenomegaly [1]. In chronic cases, some patients develop other complications that include cardiac, gastrointestinal, or both [107][108][109]. The association that this disease has with the spinal cord is through acute meningitis or nodular encephalitis, but this is in rarer cases [1,110].…”
Section: Clinical Manifestationsmentioning
confidence: 99%